Tren Penelitian Integrasi Teologi dan Psikologi di Indonesia: Systematic Literature Review - Prabowo, Paulus Dimas; Wijaya, Hengki (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2023)
Integration of theology and psychology is needed for more efficient services for the congregation. However, is this kind of integration familiar in Indonesia? This article seeks to examine the development of research on the integration of theology and psychology in Indonesia from 2003-2023. The approach used is Systematic Literature Review (SLR) with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) method. As a result, 17 articles were found that met the requirements for review and discussed the integration of theology and psychology. The authors come from 15 educational and service institutions, both ecumenical and evangelical. The branch of theology that is most studied is biblical theology, while the branch of psychology that is most studied is developmental psychology. The most dominant research synthesis is the integration of practical theology and developmental psychology. The amount of research on the integration of theology and psychology in Indonesia in the last two decades is still relatively low.